Research and Development Expenditures and Renewable Energy: An Empirical Analysis in Türkiye - Huseynli, Bahman (International Journal of Energy Economics and Policy, 2023)
In recent years, the increase in imported energy demand in Turkey significantly increases the current account deficit. In developing countries such as Turkey, foreign dependence on energy resources such as oil and natural gas, which is necessary for the realization of production, causes the current account deficit to increase. In this context, turning to renewable energy sources and increasing the amount of energy obtained from these sources is one of the alternatives to get rid of Turkey`s dependence on foreign energy in terms of energy. The aim of this study is to examine the relationship between renewable energy consumption and research and development (R&D) expenditures in Turkey for the period 1998-2021 and to determine to what extent these variables affect each other. In the study, Granger causality analysis was applied using renewable energy consumption and R&D expenditure data. According to the findings obtained in the study, a unilateral causality relationship was determined from renewable energy consumption to R&D expenditures.